Stability constraints on large-scale structural brain networks - Gray, Richard T.; Robinson, Peter A. (Frontiers in Computational Neuroscience, 2013)
Stability is an important dynamical property of complex systems and underpins a broad range of coherent self-organized behaviour. Based on evidence that some neurological disorders correspond to linear instabilities, we hypothesize that stability constrains the brain’s electrical activity and influences its structure and physiology. Using a physiologically based model of brain electrical activity, we investigated the stability and dispersion solutions of networks of neuronal populations with propagation time delays and dendritic time constants. We find that stability is determined by the spectrum of the network’s matrix of connection strengths and is independent of the temporal damping rate of axonal propagation with stability restricting the spectrum to a region in the complex plane. Time delays and dendritic time constants modify the shape of this region but it always contains the unit disk. Instabilities resulting from changes in connection strength initially have frequencies less than a critical frequency. For physiologically plausible parameter values based on the corticothalamic system, this critical frequency is approximately $10$ Hz. For excitatory networks and networks with randomly distributed excitatory and inhibitory connections, time delays and nonzero dendritic time constants have no impact on network stability but do effect dispersion frequencies. Random networks with both excitatory and inhibitory connections can have multiple marginally stable modes at low delta frequencies.